Person and Item Validity and Reliability in Essay Writing Using Rasch Model - Rahman, Yenni Arif (Universitas Islam Balitar, 2023)
This study aims to examine the reliability and validity of items and persons using the Rasch model. The students' writing skills were assessed through four constructs elaborated into twenty-four items statements in the form of a rubric. The participants were 40 EFL learners who had taken an essay writing course in TOEFL iBT class whereas the writing samples were taken in collaboration with a language center wherein the TOEFL iBT class was held. The research method employed the Rasch model as a quantitative analysis approach by using three Ministep software outputs used for data analysis: the “statistical summary output” to obtain figures and data in general, item statistics to obtain item validity, and person statistics to acquire person validity. The four assessment constructs: content, structure, diction, and mechanic fulfill item fit measured by OUTPUT MNSQ dan OUTPUT ZSTD though mechanic constructs pass the item fit with a note. The person fit order identified by INFIT MNSQ shows seven students are misfits which need further assessment to find the source of a misfit.